Some Notes About the Current Researches on the Physics of Relativistic Jets - Foschini, Luigi (Frontiers in Astronomy and Space Sciences, 2022)
Highlights in the field of relativistic jets are reviewed and critically analyzed. Given the extent of the available literature, this essay symbolically takes the baton from the outstanding and recent review by Blandford, Meier, and Readhead (2019). Therefore, I focus mostly on the results published during the latest few years, with specific reference to jets from active galactic nuclei. I conclude with some criticism and advice, which can be extended to current science at large.